Breaking boundaries: the advancements in transdermal delivery of antibiotics - Ahlam Zaid Alkilani; Rania Hamed; Batool Musleh; Zaina Sharaire (Taylor & Francis Group, 2024)
AbstractTransdermal drug delivery systems (TDDS) for antibiotics have seen significant advances in recent years that aimed to improve the efficacy and safety of these drugs. TDDS offer many advantages over other conventional delivery systems such as non-invasiveness, controlled-release pattern, avoidance of first-pass metabolism. The objective of this review is to provide an overview on the recent advances in the TDDS of different groups of antibiotics including β-lactams, tetracyclines, macrolides, and lincosamides, utilized for their effective delivery through the skin and to explore the challenges associated with this field. The majority of antibiotics do not have favorable properties for passive transdermal delivery. Thus, novel strategies have been employed to improve the delivery of antibiotics through the skin, such as the use of nanotechnology (nanoparticles, solid-lipid nanoparticles, nanoemulsions, vesicular carriers, and liposomes) or the physical enhancement techniques like microneedles and ultrasound. In conclusion, the transdermal delivery systems could be a promising method for delivering antibiotics that have the potential to improve patient outcomes and enhance the efficacy of drugs. Further research and development are still needed to explore the potential of delivering more antibiotic drugs by using various transdermal drug delivery approaches.